Pengenalan Pemasangan Sistem Proteksi Petir (SPP) Eksternal Pada Gedung di Kota Mataram - Ni Made Seniari; Rosmaliati Rosmaliati; Supriyatna Supriyatna; Abdul Natsir; Ida Ayu Sri Adnyani; Sabar Nababan (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. Indonesia is located in the tropics with an Iso Kraunic Level (IKL) of 200 strikes / km2 / year, with a relatively large risk of loss. The introduction of planning and installing a lightning protection system (SPP) was carried out for young people around the Mataram University Campus environment and was also attended by students and alumni of the Mataram University electrical engineering department. The selection of the topic and target of this activity was due to problems including (1) Lack of public understanding of the lightning phenomenon, (2) There has been no attempt by related parties to socialize ways to reduce the risk of lightning strikes, (3) Lack of public understanding of the procedure and planning for system installation external lightning protection (SPP). The external targets were: (1) Increase public understanding of the concept of lightning, (2) Increase community understanding of the impact and risk of lightning strikes, (3) Provide knowledge on how to reduce losses due to lightning strikes, (4) Provide skills in planning the installation of external SPP. The methods used were: lectures, demonstrations, question and answer, and discussion. The results achieved include: (1) Understanding of the phenomenon of lightning, (2) Understanding of the impact of direct and indirect lightning strikes, (3) Can plan the installation of external lightning installations.